Il testo e la figura Le costituzioni del Capitolo della cattedrale di Siena (1459-1464) - Pesare, Andrea (2023)
This essay aims to investigate the genesis and composition of the Constitutions of the Chapter of the cathedral of Siena, commissioned by the Sienese pope Pius II in 1459. The investigation is carried out on different levels. The point of departure is the observation of the difficulties that the chapter and the canons of the cathedral went through in the first half of the fifteenth century and of the local urban context. Thereafter the Chapter Constitutions themselves, their redaction and content are analysed. The study continues with a dating proposal and with the identification of the characters represented in the miniated frontispiece of the Constitutions' manuscript, attributed to Lorenzo di Pietro known as "il Vecchietta". Consequently, some considerations regarding the symbolic value of this work in the relationship between the canons of the Sienese cathedral and the pope are proposed.
Keywords: Canons; Cathedral Chapters; Late Middle Ages; Siena and Tuscany; Statutes